The Genesis of Epitemology In Islamic Theology - Mohd Radhi Ibrahim (Universiti Sains Islam Malaysia, 2024)
The aim of this article is to examine the origin of epistemology in Islamic theology. Therefore, I examined some early Muslim theological works on knowledge and the link between early Mutakllimun and Greek philosophy. The study indicates that although the discussion on knowledge is available in the Qur'an, the systematic appearance of epistemology in IsIamic theology gained momentum after the penetration of Greek philosophy in the Islamic world through the translation project during the 'Abbasid caliphate.